HEPATOPROTECTIVE ACTIVITY OF SAPONIN FRACTION OF OYONG SEED FLESH AND ITS COMBINATION AGAINST CCl4-INDUCED CHRONIC LIVER DAMAGE IN MALE WISTAR RAT - Rachmawati, Heni; Y. Hartiadi, R. Leonny; Fidrianny, Irda; Adnyana, I Ketut (Indonesian Journal of Pharmacy, 2013)
Saponin fraction of seed flesh of Oyong (Luffaacutangula [L.]Roxb) has been investigated to have a hepatoprotective activity in rats with fibrotic chronic liver damage. This research was conducted to evaluate whether saponin fraction of Oyongseed flesh has a hepatoprotective activity in CCl4-induced acute liver damage. Hepatoprotective activity was determined by measuring the activity of liver enzymes (SGOT, SGPT, LDH), total nitrite/nitrate level, liver index and liver histology. Saponin fraction of Oyong flesh seeds 10mg/kg BW and meniran extract 400mg/kg BW alone showed hepatoprotective activity. Administration of saponin fraction 10mg/kb BB decreased SGPT and LDH significantly over untreated group. Group given meniran extract at dose of 200mg/kg BW showed decreased on LDH, while at dose of 400mg/kg BW decreased SGPT, SGOT, and LDH significantly. Hystological observation revealed any improvement in liver morphology especially after treated with saponin fraction 10mg/kg BWand meniran extract at dose of 400mg/kg BW. However, all groups treated with combination of saponin and meniran did not show improvement both at biochemical parameter and liver histology. In conclusion, saponin extract with dose of 10mg/kg BW and meniran extract at dose of 400mg/kg BW showed hepatoprotector activity. In contrast, combination of both did not show any hepatoprotective effect and it was suspected that they have antagonist effects.Key words:hepatoprotective, CCl4-induced liver fibrosis, Luffaacutangula, Phyllanthusniruri